The political use of the figure of John Coltrane in American poetry - Šalamon, Samo (ELOPE (Ljubljana), 2007)
John Coltrane, one of the most influential and important musicians and composers of the 20th century, began to inspire jazz musicians and American poets in the 1960s with the Black Arts Movement poets. His music was interpreted and used for the promotion of political ideas in the poetics of Amiri Baraka, Sonia Sanchez, Askia Muhammad Toure, Larry Neal and others. This is the political Coltrane poetry. On the other hand, Coltrane's music inspired another kind of poets, the musical poets, which began to emerge in the 1970s. In this case, the poetry reflects the true nature of Coltrane's spiritual music quest. The poets belonging to this group, like Michael S. Harper, William Matthews, Jean Valentine, Cornelius Eady, Philip Levine, Nathaniel Mackey and others, go beyond politics, beyond race or gender. In this essay I will investigate the first type of Coltrane poetry, where Coltrane's music was used to promote the political ideas of the Black Art Movements in connection with the political movement of Malcolm X. These poets changed, rearticulated and shifted Coltrane's spiritually musical message towards the principles of the black nationalism.
Keywords: afro-ameriška poezija; ameriška književnost; ameriška poezija; Black Arts gibanje; glasba; jazz; politika; vpliv glasbe na poezijo